2021
DOI: 10.3390/nu13124411
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Aronia melanocarpa Fruit Extract from Sodium-Iodate-Induced Damages in Rat Retina

Abstract: Age-related macular degeneration (AMD) is one of the major causes of blindness in elderly populations. However, the dry form of AMD has lack of effective treatments. The fruits of Aronia melanocarpa are rich in anthocyanins. In this study, the protective effects of aronia fruit extract on rat retina were investigated using a NaIO3-induced dry AMD model. Full-field electroretinograms (ERGs) showed that b-wave amplitudes were significantly decreased and the retina structures were disordered in the model. The ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…In previous study, we found aronia anthocyanidin had protective effects on rat retina, with significant increased expression of crystallin proteins, while the effects on electroretinogram (ERG) and rat retina structure were modest 13 . There are mutual interactions between polyphenols and the gut microbiota, and increased efficacy has been observed when probiotics combined with prebiotics 14 , 15 .…”
Section: Introductionmentioning
confidence: 94%
“…In previous study, we found aronia anthocyanidin had protective effects on rat retina, with significant increased expression of crystallin proteins, while the effects on electroretinogram (ERG) and rat retina structure were modest 13 . There are mutual interactions between polyphenols and the gut microbiota, and increased efficacy has been observed when probiotics combined with prebiotics 14 , 15 .…”
Section: Introductionmentioning
confidence: 94%
“…For this reason, the protective effect of the fruit extract of Aronia melanocarpa on rat retina is so relevant. Using a NaIO3-induced dry AMD model, Xing et al [ 194 ] showed that these ACNs-rich extracts protect the rat retina, mitigating the effect of oxidative damage and upregulating at least five crystallin proteins which protect the retina ganglion cells.…”
Section: Significance Of Acns From Plants To Human Health Benefitsmentioning
confidence: 99%
“…Age-related macular degeneration (AMD) is a progressive neurodegenerative disease with a high rate of blindness, which affects vision in older individuals worldwide [ 1 ]. AMD is subdivided into two forms: wet AMD (about 5%) and dry AMD (more than 90%).…”
Section: Introductionmentioning
confidence: 99%